Fresh Semen Production of Kacang Goat (Capra Aegagrus Hircus) with Semi-Intensive Maintenance - Daoed, Denvy Meidian; Nurcholis, Nurcholis; Hardianto, Yus Rizal (Contributions of Central Research Institute for Agriculture, 2024)
The research aims to determine the effect of fresh semen production from kacang goats (Capra Aegagrus Hircus) using a semi-intensive maintenance system. The research used 4 kacang goats, including 3 males aged 2 years and 1 female aged 2 years, artificial vagina, eosin-nigrosin solution for spermatozoa staining, and physiological NaCl with 5 replications. Observations were made macroscopically (spermatozoa volume, color, pH) and microscopically (motility, viability and abnormalities). Completely Randomized Design (CDR) were used and results data were analyzed descriptively. The results showed a volume 1,2 ± 0,26 ml per ejaculate, white and cream in color, pH 4,2 ± 1,03 and mass movement + to ++. Statistical analysis show that average motility percentage of spermatozoa was 64.66 ± 4,61, average viability 69.66 ± 3.78, average abnormalities 4.6 ± 0,57, and average concentration was 2,777 ± 495. The result of research can be concluded that semi-intensive maintenance greatly affects the production of kacang goats’ fresh semen.